2019
DOI: 10.4236/health.2019.112018
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Trends and Obesity among College Going Girls of Delhi

Abstract: Background: Place of food preparation and hence consumption is an important determining factor for diet intake and consequently the risk for development of obesity. Aims: Present study attempts to examine dietary behavior among students attending undergraduate courses at Delhi University so as to assess the prevalence of overweight and obesity status using various dietary and behavioral factors triggering obesity. Methods: 201 females with age ranging from 18 to 22 years were interviewed for different socio-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Even the work preceding this currently presented piece suggests at cultivating healthy eating habits and other standard practices for stimulating an enduring lifestyle. This provides an escape from triggering the chances of progression of obesity, mainly of abdominal/central type [32]. Journal of Biosciences and Medicines…”
Section: Discussionmentioning
confidence: 99%
“…Even the work preceding this currently presented piece suggests at cultivating healthy eating habits and other standard practices for stimulating an enduring lifestyle. This provides an escape from triggering the chances of progression of obesity, mainly of abdominal/central type [32]. Journal of Biosciences and Medicines…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Gaya hidup yang berlebih dapat menjadi faktor terjadinya obesitas salah satunya adalah pola makan yang tidak teratur. 5…”
Section: Kemudahan Tersebut Memberikan Dampakunclassified
“…Moreover, people spend most of their leisure time using computers and watching television which may influence their choices to adopt consumption of unhealthy edible items. Based on all these factors, it may be concluded that lifestyle changes and social factors play an obligatory role in the onset of obesity (Mangla et al, 2019;Wadolowska et al, 2018;Kohorst et al, 2018).…”
Section: Introductionmentioning
confidence: 99%